Effects of Partial Replacement of Pork Meat with Chicken or Duck Meat on the Texture, Flavor, and Consumer Acceptance of Sausage - Namrye Lee; Han Sub Kwak; Jae-young Joo; Jinsoo Kang; Youngseung Lee (Journal of Food Quality)
This study investigated the textural and sensory characteristics of sausage, where pork meat was partially replaced with chicken or duck meat (5–30% replacement). Nine treatments including the control (100% pork) were used in this study. TPA showed hardness to be decreasing as larger proportions of chicken or duck meat were substituted for pork meat. Descriptive analysis revealed that greater amounts of chicken or duck meat produced lower intensities of hardness, springiness, and chewiness and tended to increase juiciness. The control was least liked by consumers, while the overall liking (OL) tended to increase as the chicken content rose. The OL for the duck-substituted sausage was highest in samples containing 5% duck meat and tended to decrease as more duck meat was added. The substitution of chicken or duck meat made the sausage more acceptable by adding softness and juiciness. Based on consumers’ OL, 30% of chicken or 5% of duck meat is recommended to replace pork meat in sausage.